2013
DOI: 10.1016/j.psychres.2012.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Neural basis of implicit memory for socio-emotional information in schizophrenia

Abstract: Individuals with schizophrenia are impaired in processing social signals such as facial expressions of emotion. Perceiving facial expressions is a complex process that depends on a distributed neural network of regions involved in affective, cognitive, and visual processing. We examined repetition priming, a non-conscious form of perceptual learning, to explore the visual-perceptual processes associated with perceiving facial expression in people with schizophrenia. Functional magnetic resonance imaging (fMRI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
(78 reference statements)
0
2
0
1
Order By: Relevance
“…Finally, the aberrant brain reactivity to irrelevant stimuli in schizophrenia may be explained by reduced neural habituation to emotionally neutral faces ( 52 ), but this possibility has been examined in only one study ( 32 ).…”
Section: Explanatory Modelsmentioning
confidence: 99%
“…Finally, the aberrant brain reactivity to irrelevant stimuli in schizophrenia may be explained by reduced neural habituation to emotionally neutral faces ( 52 ), but this possibility has been examined in only one study ( 32 ).…”
Section: Explanatory Modelsmentioning
confidence: 99%
“…In the other hand, Walther et al (2009) found both encoding and face recognition abnormalities and those associated to a low activation of the right fusiform face area. A more recent work has shown impairment in memory for faces, despite the expression in patients with schizophrenia in a repetition priming task, and the decreasing in performance was associated to an abnormal activation of the left fusiform gyrus (Schwartz et al, 2012).…”
Section: Social Intelligence and Deficits In Schizophreniamentioning
confidence: 93%
“…Las personas con esquizofrenia presentan un deterioro en el procesamiento de señales sociales como las expresiones faciales de emoción. La percepción de expresiones faciales es un proceso complejo que depende de una red neuronal distribuida dentro de las regiones implicadas en el procesamiento visual, cognitivo y afectivo; en un estudio se examinó el priming de repetición, se exploraron los procesos perceptivos visuales asociados a la percepción de la expresión facial en personas con esquizofrenia; como resultado el priming fue normal en los pacientes con esquizofrenia, pero, como era de esperar, la memoria de reconocimiento para las expresiones faciales estaba deteriorada (18) . En otro estudio se observó que los pacientes esquizofrénicos logran un priming tan alto como el de los controles en la tarea de decisión léxica; en contraste, sólo los controles mostraron priming significativo en la tarea de verificación de la categoría.…”
Section: Introductionunclassified